Marine Oomycetes of the Genus Halophytophthora Harbor Viruses Related to Bunyaviruses - Botella, Leticia; Janoušek, Josef; Maia, Cristiana; Jung, Marilia Horta; Raco, Milica; Jung, Thomas (Frontiers in Microbiology, 2020)
We investigated the incidence of RNA viruses in a collection of Halophytophthora spp. from estuarine ecosystems in southern Portugal. The first approach to detect the presence of viruses was based on the occurrence of dsRNA, typically considered as a viral molecule in plants and fungi. Two dsRNA-banding patterns (∼7 and 9 kb) were observed in seven of 73 Halophytophthora isolates tested (9.6%). Consequently, two dsRNA-hosting isolates were chosen to perform stranded RNA sequencing for de novo virus sequence assembly. A total of eight putative novel virus species with genomic affinities to members of the order Bunyavirales were detected and their full-length RdRp gene characterized by RACE. Based on the direct partial amplification of their RdRp gene by RT-PCR multiple viral infections occur in both isolates selected. Likewise, the screening of those viruses in the whole collection of Halophytophthora isolates showed that their occurrence is limited to one single Halophytophthora species. To our knowledge, this is the first report demonstrating the presence of negative (−) ssRNA viruses in marine oomycetes.